Design and investigation on microstructure and properties of Mo-Nb-Ti-V-Si eutectic refractory multi-principal element alloys - Duo Dong; Wentao Jiang; Jiangfei Yan; Dongdong Zhu; Ning Fang; Tengfei Ma; Xiaohong Wang; Ye Wang (Journal of Materials Research and Technology)
The design of high-performance refractory multi-principal element alloys (RMPEAs) for elevated-temperature applications requires precise control of eutectic microstructures through composition optimization. In this study, we employed JMatPro software with CALPHAD methodology to predict the solidification paths of (Mo0.7NbTiV0.3)100-xSix (x = 6, 12, 18, and 24) alloys, identifying 18 at.% Si as the eutectic composition through characteristic cooling curve analysis. The results showed a microstructure evolution from hypoeutectic (BCC dendrites + interdendritic M5Si3 when x ≤ 18 at. %) to fully eutectic (when x = 18 at. %) and hypereutectic (primary M5Si3 + eutectic when x = 24 at. %). Furthermore, the introduction of Si significantly enhances the mechanical properties of the alloy, and the compressive yield strength of (Mo0.7NbTiV0.3)88Si12 alloy can reach 1468 MPa at 600 °C, which is nearly 25 % higher than that of (Mo0.7NbTiV0.3)94Si6 alloy. The main reason for the significant enhancement in performance is the second phase strengthening brought about by the increase in the volume fraction of the M5Si3 phase. These findings establish an efficient computational-experimental approach for developing eutectic RMPEAs with tailored high-temperature performance through controlled Si addition.